Identification of an anti-inflammatory action of exosome release in P2Y4 loss-mediated cardioprotection - Diaz Villamil, Esteban; Rouvier, Paul; Horckmans, Michael; De Roeck, Lucas; Hendrickx, Erika; Conrard, Louise; Communi, Didier (Frontiers in Pharmacology, 2025)
IntroductionExosomes are major actors in the progression of cardiovascular diseases and potential associated-treatments. We showed previously that inactivation of the mouse P2Y4 nucleotide receptor induces a protection against myocardial infarction in the left anterior descending artery ligation model, characterized by smaller infarcts and reduced cardiac fibrosis and inflammation, compared to wild-type mice. This cardioprotection was associated with adiponectin and PD-L1 overexpression, regulatory leukocyte increase, and adipocyte beiging in the pericardial adipose tissue of P2Y4-null mice. We investigated here the contribution of exosome release in the cardioprotection observed in ischemic P2Y4-null mice.Methods and resultsInterestingly the reduction of cardiac fibrosis and T cell infiltration observed in P2Y4-null compared to wild-type ischemic heart was abolished after intraperitoneal injection of the exosome inhibitor GW4869 during myocardial infarction onset, as previously observed using an anti-PD-L1 blocking antibody. Additionally, GW4869 injection totally inhibited the increase in plasma PD-L1 level observed in P2Y4-null ischemic mice, as well as the higher T cell apoptosis in their pericardial adipose tissue, compared to wild-type mice. We observed increased expression of CDH13/T-cadherin, essential for adiponectin-driven exosome biogenesis, in P2Y4-null pericardial adipose tissue. Plasma exosomes were isolated from wild-type and P2Y4-null ischemic mice and characterized using nanoparticle tracking analysis and transmission electron microscopy experiments, as well as Western blot analysis of CD63 exosome marker and adiponectin expression. Our data support an increase in exosomes from adipocyte origin in the plasma of P2Y4-null ischemic mice. Flow cytometry experiments showed that P2Y4-null ischemic mice displayed an increased level of PD-L1+ plasma exosomes compared to wild-type ischemic mice. We finally demonstrated the capacity of total plasma exosomes from P2Y4-null ischemic mice to polarize macrophages into the anti-inflammatory M2c phenotype in vitro. M2c macrophages can inhibit T cell activation through PD-L1 regulation and play a central role in the resolution of cardiac inflammation to promote cardiac repair.DiscussionThese data support the role of the release of anti-inflammatory exosomes, and more particularly the exosomal form of PD-L1 and adiponectin, in P2Y4 loss-mediated cardioprotection. The study of regulators of cardioprotective exosomes could lead to the development of novel anti-inflammatory therapies to improve myocardial infarction outcome.